Electroencephalographic and early communicative abnormalities in Brattleboro rats. Issue 5 (20th October 2013) - Lin, Robert E.; Ambler, Lauren; Billingslea, Eddie N.; Suh, Jimmy; Batheja, Shweta; Tatard‐Leitman, Valerie; Featherstone, Robert E.; Siegel, Steven J.
Abstract: Reductions in the levels of the neuropeptide vasopressin (VP) and its receptors have been associated with schizophrenia. VP is also critical for appropriate social behaviors in humans as well as rodents. One of the prominent symptoms of schizophrenia is asociality and these symptoms may develop prodromally. A reduction in event‐related potential (ERP) peak amplitudes is an endophenotype of schizophrenia. In this study, we use the Brattleboro (BRAT) rat to assess the role of VP deficiency in vocal communication during early development and on auditory ERPs during adulthood. BRAT rats had similar vocal communication to wild‐type littermate controls during postnatal days 2 and 5 but the time between vocalizations was increased and the power of the vocalizations was reduced beginning at postnatal day 9. During adulthood, BRAT rats had deficits in auditory ERPs including reduced N40 amplitude and reduced low and high gamma intertrial coherence. These results suggest that the role of VP on vocal communication is an age‐dependent process. Additionally, the deficits in ERPs indicate an impairment of auditory information processing related to the reduction in VP. Therefore, manipulation of the VP system could provide a novel mechanism for treatment for negative symptoms of schizophrenia. Abstract : e00100 Abstract : In this study we use the Brattleboro (BRAT) rat to assess the role of VP deficiency in vocal communication during early development and on auditory ERPs during adulthood. BRAT rats had similar vocal communication to wild type littermate controls during post‐natal day 2 and 5 but the time between vocalizations was increased and the power of the vocalizations was reduced beginning at post‐natal day 9. During adulthood, BRAT rats had deficits in auditory ERPs including reduced N40 amplitude and reduced low and high gamma inter‐trial coherence.